Better Justice Through Better Science-Technology? - G. L. Lima, Thallita. author. (orcid)0000-0003-3488-349X Link aut Link
XVIII, 252 p. 13 illus.
Keywords: This book examines how algorithms are reshaping security and criminal justice, revealing their profound social and political implications. From intelligence agencies and police forces to courtrooms, tools like facial recognition are redefining how security is imagined and enacted worldwide. Yet, alongside promises of efficiency and objectivity, these systems frequently fail—exposing tensions around their epistemic authority and legitimacy. Focusing on biometric data and cases like Clearview AI in the United States, the book unpacks the entanglements between security professionals, legal actors, and algorithmic systems, showing how these technologies gain stability even amid errors and disputes. Drawing on Critical Security Studies, Science and Technology Studies, and feminist critiques of technoscience, it offers a multidimensional analysis of “algorithmic reason,” its narratives of “better justice” or “enhanced security,” and the ethical and political challenges they generate. A vital resource for scholars, practitioners, policymakers, and anyone concerned with the societal impacts of emerging technologies. Thallita G. L. Lima is a professor at the Federal Rural University of Rio de Janeiro and Research Coordinator at the Center for Studies on Security and Citizenship (CESeC). She holds a PhD and Master’s in International Relations from PUC-Rio, focusing on critical security, algorithmic governance, and security technologies.